Algorithmic Art in the School Curriculum: Thinking beyond disciplines - Grabowski, Susanne; Nake, Frieder (MediaEducation: Journal for Theory and Practice of Media Education, 2019)
As a result of the algorithmic revolution, many of us are now carrying a high-performance computer in their pockets, and have others waiting at home. With the Internet, these computers have been integrated into an attractive medium. A new kind of thinking is emerging with this unique turn-over of all the technological infrastructure of culture: algorithmic thinking. Only few realise that this kind of thinking is a thinking towards computability, and to the machine. As such it is narrowing thought. Humans are capable of continued interpretation without limits. The world of machines, on the other hand, must necessarily limit interpretation to unique determination. Current culture is caught in this contradiction. In art, closing-down algorithmics encounters opening-up aesthetics. In algorithmic art, now more than fifty years old, both meet. In this encounter we expect chances for educational processes. What should young people know about impacts of their way of communicating? How can they come to understand that their way of communication depends on the permanent activity of algorithms and data-structures? How can they see that a semiotic layer of reality is simulating and preparing for the changes of the physical world? Simulation and automation have always been subject matter of computing, algorithms and data-structures are its means. Design of contents and instrumental use have always belonged to media education. What of this must today become part of a general education, and how? – We are concerned about this question in the context of introducing the discipline of computing in primary school already. This essay is about «algorithmic thinking» which is basic for an understanding of digital computing. We show examples of how to learn algorithmic thinking by studying works of art, and what role there is for algorithmic art, in particular. Our discussion is on the level of disciplinary skills. But we see how important it becomes to leave behind the confines of discipline if we want to achieve good general education.